2020
DOI: 10.3892/mmr.2020.11332
|View full text |Cite
|
Sign up to set email alerts
|

Weighted gene co‑expression network analysis identifies key genes from extracellular vesicles as potential prognostic biomarkers for congenital pulmonary stenosis

Abstract: consisted of mrnas, micrornas and long non-coding rna. overall, 26 modules were identified containing 16,394 genes. all modules were independent of each other. one particular module, referred to as the blue module, was markedly different between the two groups. a total of 735 hub genes in the blue module were identified, of which 33 were visualized, demonstrating the connection between these hub genes. Go enrichment analysis demonstrated that the analyzed hub genes were enriched in 'glucose transport', 'aTP-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…First, samples of synovium data set GSE55235 were clustered to detect and eliminate outliers using the flashClust function. 20 The independence and average connectivity degrees of the coexpression networks were mainly determined by a power value. 21 Then, suitable soft thresholding power value was selected using the pickSoftThreshold function of the WGCNA algorithm if the independence degree was >0.85.…”
Section: Methodsmentioning
confidence: 99%
“…First, samples of synovium data set GSE55235 were clustered to detect and eliminate outliers using the flashClust function. 20 The independence and average connectivity degrees of the coexpression networks were mainly determined by a power value. 21 Then, suitable soft thresholding power value was selected using the pickSoftThreshold function of the WGCNA algorithm if the independence degree was >0.85.…”
Section: Methodsmentioning
confidence: 99%
“…Both studies isolated EVs from maternal blood before profiling RNA expression. Jin et al [135] identified miRNAs that were differentially expressed in pregnant women carrying a child with ventricular septal defects compared to the control group, whilst Huang et al [136] identified differences in long non-coding RNA (lncRNA) expression in pregnant women carrying a child with pulmonary stenosis. In another study, Gu et al [137] identified differentially expressed lncRNA in maternal blood from a mixed cohort of CHD cases (including both ventricular and atrial septal defects as well as Tetralogy of Fallot) versus healthy controls.…”
Section: Evidence For Evs From the Foetal Nervous And Cardiovascular ...mentioning
confidence: 99%